A Note on Intraday Event Studies. Issue 3 (27th May 2019) - Marshall, Ben R.; Nguyen, Nick; Visaltanachoti, Nuttawat
Abstract: We investigate the specification and power of intraday event study test statistics. Mean, market, and matched firm models generate well-specified return results for a range of intervals up to 60 min around the event. These models detect return shocks equivalent to one spread in one-minute interval data and three spreads in longer intervals. Researchers using intraday return event studies can, therefore, be confident in their robustness. Some volume event study approaches have reasonable power but they are not generally well specified, while a matched-firm approach gives the best combination of specification and power for spread event studies.